Pengaruh Penambahan Lateks dan Filler Semen pada Campuran AC-BC terhadap Karakteristik Marshall - M. Safiq Zahibul Fadila; M. Enriko Tosulpa; Farida Juwita; Rizki Pratama; Rahmad Hidayat Lendrian; Gran Silmi Kholifawati (Lembaga Teewan Journal Solutions, 2026)
This study evaluates the effect of liquid natural rubber latex and cement filler on the Marshall characteristics of Asphalt Concrete–Binder Course (AC-BC). A laboratory experiment was conducted using two asphalt contents (4.5% and 5.5%) and four latex contents (0%, 8%, 10%, and 12% by asphalt weight). Three specimens were prepared for each combination, resulting in 24 Marshall specimens. The evaluated parameters were voids in mixture (VIM), voids in mineral aggregate (VMA), voids filled with bitumen (VFB), stability, flow, and Marshall Quotient (MQ). At 4.5% asphalt, the 12% latex mixture produced the highest stability of 1,036.8 kg and an MQ of 343.44 kg/mm. At 5.5% asphalt, the 8% latex mixture produced the highest stability of 1,085.0 kg and an MQ of 371.46 kg/mm. All modified mixtures satisfied the minimum stability requirement and the specified flow range. The control mixture at 5.5% asphalt had a VIM of 2.87%, below the 3–5% requirement, whereas latex-modified mixtures remained within the range. The response was non-linear, indicating an optimum balance between asphalt, latex, and cement filler. Latex addition can improve load-bearing capacity and mixture stiffness when applied at an appropriate dosage.